Comparison of the Learning Outcomes in the Ecology Course Using Socio-Scientific Problem based Learning and Stimulus Environment Problem Solving Models - Kusumadani, Annur Indra; Nabila , Albertha Fausta; Najwa, Nadhifa (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Learning that is still dominated by teacher-centered approaches tends to result in passive student participation and low learning outcomes. This study aims to compare the effectiveness of the Socio-Scientific Problem-Based Learning (SSPBL) model and the Stimulus Environment Problem Solving (SEPS) model in improving student learning outcomes in the Ecology course. The research employed a quasi-experimental design involving two groups of fourth-semester Biology Education students at Universitas Muhammadiyah Surakarta in the even semester of the 2023/2024 academic year. Each group consisted of 20 students; one was taught using the SSPBL model, and the other using the SEPS model. Data were analyzed using the independent sample t-test and effect size analysis.The results showed that the SSPBL group achieved significantly higher cognitive learning outcomes than the SEPS group in both Cycle I (sig. = 0.041) and Cycle II (sig. = 0.049). The effect size results further confirmed the high effectiveness of the SSPBL model, with values of 2.846 (Cycle I) and 3.413 (Cycle II), categorized as